'The Elephant in the Room': Corporate Tax Avoidance & Business and Human Rights. Issue 1 (12th August 2016) - DARCY, Shane
Abstract: This article addresses tax avoidance by companies in the context of the emerging field of business and human rights. It describes the mechanics of corporate tax avoidance and the human costs of such practices. It then considers the extent to which tax issues have been addressed by corporate social responsibility, before turning to business and human rights and assessing the potential value of the United Nations Guiding Principles on business and human rights in this context. The article draws on the experience of Ireland, given the country's connection to abusive tax practices associated with large multinational corporations and its support for the United Nations Guiding Principles on business and human rights.